A Critical Review on the Book Tazkirat Al-Awliya - Masoumeh Amirkhanlou (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The publication and textual criticism of Attar of Nishapur’s “Tazkerat al-Awliya”, which is considered as one of the most important texts in Persian prose, was done in 1398 by Dr. Mohammad Reza Shafi'i Kadkani. More than a century has passed since the first textual criticism of “Tazkerat al-Awliya” by Reynold Alleyne Nicholson, but the new work that has been made is in many ways superior to the works of others; because the editor has largely provided a text close to Attar's language by dealing with multiple manuscripts and providing a textual criticism. In addition to this, it is necessary to mention the useful comments, the detailed introduction, and the acquisition of the main sources of the mystics' words in Tazkerat and their memoirs and cultures. The present article intends to point out some of the shortcomings and mistakes in the text of the book while pointing out the advantages and benefits of the new work. These shortcomings include typographical errors, incomplete or incorrect references, ambiguity in the method of textual criticism, structural and content confusion.